A series of nonionic surfactants for lignite flotation and adsorption performance. Issue 1 (2nd January 2021) - Wang, Jie; He, Yaqun; Zhao, Xiaolu; Wang, Shuai; Wei, Hua; Zhang, Tao; Zhu, Xiangnan; Lu, Zhaolin
ABSTRACT: Nonionic surfactants have been applied to improve the lignite floatability in the flotation process. In this paper, Inner Mongolia lignite was pretreated by three type surfactants, including sorbitan monolaurate, sorbitan monostearate, and sorbitan monooleate, respectively. It was investigated that the effect of the length and saturability of hydrocarbon chain on the collectivity and selectivity of surfactant. The flotation results indicated that the optimum efficiencies were found at the dosages of about 35 kg/t for the three surfactants. However, the recovery of combustible material of lignite pretreated by sorbitan monolaurate is comparatively low, which may relate to the weak collectivity of this shorter hydrocarbon chain surfactant. On the other hand, XPS results showed that the C1s can be fitted to C-C, C-H, C-O, and COO- with the contents of 10.99%, 9.19% and 2.11% on the raw lignite surface, respectively. After the pretreatment, the contents of hydrophobic C-C, C-H were increased to 13.53%, 16.07% and 17.18% for the three surfactants. Obviously, the hydrophobic functional groups were much higher after pretreated by sorbitan monooleate, which was corresponded with the better flotation results. Therefore, the longer and unsaturated hydrocarbon chain in sorbitan monooleate molecule is beneficial for the collectivity and selectivity for lignite.